Study of the Rheological Behavior of Polyamide 5,6 (PA5,6 - Eltahir, Yassir A.; Saeed, Haroon A. M.; Ahmed, Mutasim A.; Yong, He; Yimin, Wang (Gezira Journal of Engineering and Applied Sciences, 2018)
The rheological behavior of polymer melts and polymer solutions are of great importance in polymer processing, particularly for the analysis and design of processing operations as well as understanding the relationship between structures and properties of the final-products. The objective of the present work was to investigate the rheological behavior of polyamide 5,6  (PA5,6) to obtain information on the effect of temperature on the melt behavior of polyamide 5,6 compared to that of polyamide 6. The rheological properties of polyamide 5,6 (PA5,6) have been studied by means of a Haake  rheometer. The effect of temperature on the storage modulus, loss modulus, and complex viscosity was studied. The obtained results showed that the complex viscosity, storage modulus, and loss modulus of PA5,6 and PA6 decrease with increase of the temperature. It is worth noting that the complex viscosity of PA5,6 remains almost constant showing a Newtonian behavior, on the other hand, the complex viscosity of PA6 slightly decreases with the increase of shear rate exhibits a much nearly Newtonian behavior. Similar behavior was observed for other polyamides such as polyamide 6.6 and polyamide 6.,10